Orang Asli Identity In The Nation-State - Ibrahim, Zawawi (Journal of Malaysian and Comparative Law, 2019)
A challenging task facing anthropologists concerned with indigenous minorities (in this context, the Orang Asli of Peninsular Malaysia) and their identity question is how best to represent and mediate the differentiated tones of ’the Other’ and yet at the same time, convey in the analysis, the wide relational, historical and political economic processes which locate these expressions of identity.